2017
DOI: 10.1021/jacs.7b01946
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Charge Shifts and Electron Transfer in Viologen–Tetraphenylborate Complexes: Push–Pull Character of the Exciplex

Abstract: Viologen-tetraarylborate ion-pair complexes were prepared and investigated by steady-state and time-resolved spectroscopic techniques such as fluorescence and femtosecond transient absorption. The results highlight a charge transfer transition that leads to changes in the viologen structure in the excited singlet state. Femtosecond transient absorption reveals the formation of excited-state absorption and stimulated emission bands assigned to the planar (k < 10 s) and twisted (k ∼ 10 s) structures between two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 30 publications
0
72
0
Order By: Relevance
“…1 Viologens form ion-pair charge transfer (IPCT) complexes with many inorganic and organic anions of electron donor nature. For example, N,N 0 -dimethyl-4,4 0bipyridinium (methyl viologen, MV 2+ ) forms MV 2+ X À ion pairs with anions X À = F À , Cl À , Br À , I À , perchlorate, sulphate 2 and tetraphenylborate, [3][4][5] which have a specific charge transfer band in their absorption spectra. It falls between 350 and 500 nm, depending on the solvent and the counter anion.…”
mentioning
confidence: 99%
“…1 Viologens form ion-pair charge transfer (IPCT) complexes with many inorganic and organic anions of electron donor nature. For example, N,N 0 -dimethyl-4,4 0bipyridinium (methyl viologen, MV 2+ ) forms MV 2+ X À ion pairs with anions X À = F À , Cl À , Br À , I À , perchlorate, sulphate 2 and tetraphenylborate, [3][4][5] which have a specific charge transfer band in their absorption spectra. It falls between 350 and 500 nm, depending on the solvent and the counter anion.…”
mentioning
confidence: 99%
“…This phenomenon corresponds to negative solvatochromism [41]. More recently, Santos et al reported on the photoinduced charge shifts in some viologen-tetraphenylborate complexes, which were studied by means of steady-state and time-resolved spectroscopic techniques [24]. An interesting reversible on-off photoswitching aptitude was observed in the solid state.…”
Section: Charge Transfer Complexes Of Viologensmentioning
confidence: 98%
“…In all these cases, the reducing species transfer one electron to the electron-deficient viologen skeleton in an inter-or intra-molecular fashion. Light irradiation can trigger charge transfer from the counter anion of a viologen (BPh4) − [24], [Fe II (CN)6] 4− [25], etc. ( Figure 2b) and the photochromism of viologens is attributed to this effect [18].…”
Section: The Strong Electron-withdrawing Character Of Viologensmentioning
confidence: 99%
See 1 more Smart Citation
“…The chromic behaviour of viologen-based polymers has been mainly related to a variety of structural factors, such as the electron-donating ability of the donor, the electronaccepting ability of the acceptor, the packing arrangement, the intermolecular interactions, and the orientation, position and especially the distance between the electron donor and acceptor (Sun et al, 2018;Santos et al, 2017), which may be easily studied in detail for the most versatile chromic materials. However, in this field, determining the decisive impact on photochromism of viologen-based compounds is still an obstacle, because there is more than one possible factor, e.g.…”
Section: Introductionmentioning
confidence: 99%